Proceedings of Eurosensors 2017, Paris, France, 3–6 September 2017 2017
DOI: 10.3390/proceedings1040379
|View full text |Cite
|
Sign up to set email alerts
|

High Accuracy MEMS Pressure Sensor Based on Quartz Crystal Resonator

Abstract: This paper reports a high accuracy oil-filled MEMS absolute pressure sensor based on quartz crystal double-ended tuning fork (DETF) resonator, which is suitable for application in ocean, petroleum, meteorological, aerospace and spacecraft field, etc. The pressure sensing unit is mainly composed of DETF resonator, diaphragm and back cavity structure. These pieces are all fabricated by quartz crystal using MEMS process, and are bonded together as 'sandwich' structure to form the absolute pressure sensing unit us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, these methods have their own drawbacks in the compensation processes. Wang, J. et al reported a resonant pressure sensor that employs a temperature sensor for temperature compensation [19,20]. This method is only suitable for a slowly varying temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods have their own drawbacks in the compensation processes. Wang, J. et al reported a resonant pressure sensor that employs a temperature sensor for temperature compensation [19,20]. This method is only suitable for a slowly varying temperature.…”
Section: Introductionmentioning
confidence: 99%
“…As a mass-sensitive sensor, the quartz crystal microbalance (QCM) works on the principle of frequency shift. Te sensor's resonance frequency changes according to the amount of the absorbing or desorbing molecule on the sensor surface [1] or by other infuences such as force [2,3], friction [4], and others. A frequency counter is used as a data acquisition system.…”
Section: Introductionmentioning
confidence: 99%
“…To measure dynamic changes, piezoelectric sensors can be used, but they are not sensitive for static pressure [ 7 ]. Recent developments for highly accurate sensors are based on resonant detection mechanisms [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%